Digital rights identification as an object of accounting and control - A. V. Bodiako; S. V. Ponomareva; T. M. Rogulenko (Учёт. Анализ. Аудит, 2022)
The intensive development of digital technologies, their penetration into business and everyday life calls for the assessment of theoretical validity and practical feasibility of including the concepts of “digital rights” in civil law legislation. The purpose of the study is to develop a methodology for identifying digital rights as an object of accounting and control. The article analyzes the definitions of the concept “digital rights”, “obligation and other rights”, evaluates the forms of digital rights implementation and restrictions on the disposal of digital rights, proposed in Law No. 34-FZ. The authors consider the applied value of the phenomenon of digital rights not only in civil paper work, but also in accounting and control processes. The concepts developed by accounting methodologists to post transactions with digital rights in ledgers are revealed. On the basis of generalization of the initial technological foundations of asset tokenization in business projects, a conclusion is made that a shared problem in digital rights management involves the choice of digital algorithms, financial platforms for their issuance and circulation. The analysis of the Russian and international rules for the identification of digital financial assets (DFA) (tokens) as an object of the accounting policy of companies and their use in preparation of reports makes it possible to state that DFA can be considered a financial instrument with all subsequent accounting and control and analytical operations only when a specific right, for example, participation in the replacement of real shares, is exercised. It is recommended to make some amendments related first, to the accounting and reporting methodology to facilitate the identification and assessment of digital rights holders (investment tokens) that replace securities, and, second, to account 58 “Financial Investments”, namely to open an additional subaccount to account for securities which are replaced by digital assets or digital currency.